Poems - Cawein, Madison Julius, 1865-1914; Howells, William Dean, 1837-1920 (Salt Lake City, UT : Project Gutenberg, 2005)
"Poems" by Madison Julius Cawein is a collection of poetry published in the early 20th century. The volume features a selection of works by Cawein, showcasing his connection to nature, exploration of themes related to love and youth, and a rich, lyrical style that evokes the beauty of the natural world. The collection is prefaced by a foreword from the well-known author William Dean Howells, who highlights Cawein's imaginative ability to imbue ordinary scenes of nature with deep emotional resonance. The opening of this poetry collection introduces the reader to the thoughtful curation of Cawein's verses, which spans nearly three decades of his poetic career. In the introductory note, Cawein expresses his intention to cover the full range of his poetic exploration, primarily focusing on themes of nature, human emotion, and the passage of time. The early poems featured include vivid depictions of the beauty of the natural world, such as the allure of spring blossoms, the haunting calls of wildlife, and the silent wisdom of trees. Overall, the beginning of the book establishes an inviting tone, encouraging readers to immerse themselves in Cawein's poetic landscapes, both inward and outward. (This is an automatically generated summary.)
Release date is 2005-03-01
Produced by Eric Eldred, S.R. Ellison, and the Online Distributed Proofreading Team
Keywords: American poetry